Survey of respiratory disease associated with Mycoplasma gallisepticum in British gamebirds (2016–2019): In vitro antibiotic sensitivity, pathology and detection of other pathogens. (25th August 2022) - Welchman, David; Tasker, John; Poulos, Christopher; Ellis, Christine; Bradbury, Janet M.
Abstract: Background: The causes of respiratory disease in British gamebirds were investigated during 2016–2019 following concerns about poorer responses to antibiotic treatment. Emphasis was placed on Mycoplasma gallisepticum, but other possible bacterial and viral causes were included, along with gross and histopathological examination. Methods: Clinical respiratory disease outbreaks were investigated. Results: Mycoplasma gallisepticum was detected by PCR in 65 of 69 outbreaks in pheasants and partridges and isolated from 56 of these. Partial mgc2 gene sequences from 28 M. gallisepticum isolates were compared, and 26 proved identical, suggesting the prevalence of a dominant sequence type. Minimum inhibitory concentration values for tiamulin, tylosin, tylvalosin, doxycycline and tetracycline were significantly higher than the reference strain but could not be correlated with treatment failures. Other bacterial species were isolated from sinuses but were not consistently correlated with disease. RT‐PCRs detected coronaviruses in 18% of 49 outbreaks and avian metapneumovirus in 8%. Histopathological lesions were typical of M . gallisepticum sinusitis and significantly associated with M . gallisepticum PCR outbreak positivity. Conclusion: Mycoplasma gallisepticum remains an important cause of respiratory disease in gamebirds. Synergism with other pathogens may have played a role in some outbreaks. Specific reasons for variable responses to antibacterial treatment were not identified.